Meningkatkan Mutu Pembelajaran Melalui Kompetensi Guru Dan Dukungan Komite Sekolah - Alvionita, Kurnia Alfa; Purwanto, Nurtanio Agus (Publikasi Pendidikan, 2025)
This study aims to empirically examine the extent to which teacher competence, the availability of educational facilities and infrastructure, and the role of school committees contribute to improving the quality of learning in public elementary schools in Kurun District, Gunung Mas Regency. This study uses a quantitative approach with an ex post facto design, where all variables are observed after the event has occurred without any researcher intervention. The study population includes all elementary school teachers, with 182 respondents selected through stratified random sampling techniques to represent each population stratum proportionally. The research instrument is a closed questionnaire based on Likert and Guttman scales that have undergone validity and reliability testing. The data analysis process was carried out using descriptive and inferential statistics, including classical assumption tests and simple and multiple linear regression analyses using IBM SPSS Statistics software version 27. The results of the analysis indicate that teacher competence and the role of school committees have a positive and significant influence on the quality of learning, both partially and simultaneously. Meanwhile, the availability of facilities and infrastructure has a negative influence. These results confirm that increasing teacher professional capacity, equalizing educational facilities, and optimizing the function of school committees are key factors in realizing quality learning at the elementary education level.